2019
DOI: 10.1161/circresaha.119.314682
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2017 ACC/AHA Guideline for High Blood Pressure on Evaluating Gestational Hypertension–Associated Risks for Newborns and Mothers

Abstract: Rationale: In 2017, the American College of Cardiology (ACC)/American Heart Association (AHA) released a new hypertension guideline for nonpregnant adults, using lower blood pressure values to identify hypertension. However, the impact of this new guideline on the diagnosis of gestational hypertension and the associated maternal and neonatal risks are unknown. Objective: To estimate the impact of adopting the 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 49 publications
4
35
2
2
Order By: Relevance
“…We observed a prevalence of 5% for HDP in this cohort, which is consistent with findings that reported a prevalence of 4.2% for HDP in China [29]. Our results were supported by a study which suggested that exposure to high levels of PM 2.5 during early pregnancy was associated with increased prevalence of HDP [12].…”
Section: Discussionsupporting
confidence: 92%
“…We observed a prevalence of 5% for HDP in this cohort, which is consistent with findings that reported a prevalence of 4.2% for HDP in China [29]. Our results were supported by a study which suggested that exposure to high levels of PM 2.5 during early pregnancy was associated with increased prevalence of HDP [12].…”
Section: Discussionsupporting
confidence: 92%
“…[5][6][7] To our knowledge there has only been a single prior study examining the impact of applying the 2017 ACC/AHA on the prevalence of gestational hypertension, which drew its data from a group of 16 345 women from China. 8 In that study, the authors reported a 20.9% increase in the prevalence of gestational hypertension defined using the 2017 ACC/AHA criteria compared with the 7.8% increase in the current study. Although the…”
Section: Jama Network Open | Cardiologycontrasting
confidence: 39%
“…[5][6][7] To our knowledge, this is the first US-based study to examine the application of the lower threshold to women throughout the duration of pregnancy, rather than only prior to 20 weeks' gestation. 8 The objectives of this investigation were to estimate changes in diagnostic information that may result from applying the 2017 ACC/AHA BP guideline criteria to pregnant women and their offspring.…”
Section: Introductionmentioning
confidence: 99%
“…We observed a prevalence of 5% for HDP in this cohort, which is consistent with findings that reported a prevalence of 4.2% for HDP in China (19). Previous studies have reported inconsistent results for the association between PM 2.5 exposure and risk of HDP.…”
Section: Discussionsupporting
confidence: 92%